2008
DOI: 10.1530/eje-08-0039
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypocaloric diet-induced weight loss in obese women on plasma apelin and adipose tissue expression of apelin and APJ.

Abstract: Objective: Apelin is a novel adipokine acting on APJ receptor, regulated by insulin and tumor necrosis factor-a (TNF-a) in adipose tissue (AT). Plasma apelin levels are increased in obese hyperinsulinemic subjects. The aim was to investigate whether the hypocaloric diet associated with weight loss modifies the elevated plasma apelin levels and the expression of apelin and APJ receptor in AT in obese women. Design and methods: Fasting plasma levels of apelin and TNF-a as well as mRNA levels of apelin and APJ in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
92
5
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(111 citation statements)
references
References 14 publications
7
92
5
7
Order By: Relevance
“…4 and 5). The notion that apelin signaling is a beneficial physiological response to oxidative stress in adipose is supported by the previous observation that the plasma apelin level is elevated in obesity (25,26). It also explains the previous observations in mice that apelin treatment leads to a significant decrease in plasma lipid hydroperoxide (an index of systemic oxidative stress) (23), and improves glucose uptake in adipose tissue (18).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…4 and 5). The notion that apelin signaling is a beneficial physiological response to oxidative stress in adipose is supported by the previous observation that the plasma apelin level is elevated in obesity (25,26). It also explains the previous observations in mice that apelin treatment leads to a significant decrease in plasma lipid hydroperoxide (an index of systemic oxidative stress) (23), and improves glucose uptake in adipose tissue (18).…”
Section: Discussionmentioning
confidence: 58%
“…However, its regulations of oxidative stress in adipocytes have never been investigated. Considering that apelin expression in adipocytes is up-regulated in obesity (17) and its plasma level is increased in obese subjects (25,26), we speculate that apelin may act as the feedback control to limit obesity-associated oxidative stress.…”
mentioning
confidence: 92%
“…Changes in apelin levels after weight loss or bariatric surgery in obese individuals were also investigated. Dietinduced weight loss decreases apelin levels in moderate obese women [154] but not significantly in patients with the MetS [155] or in obese children [156] . Bariatric surgery resulted in a significant decrease in apelin levels only in morbidly obese patients exhibiting impaired fasting glucose or type 2 diabetes before surgery [151] .…”
Section: Apelinmentioning
confidence: 90%
“…Insulin has been shown to be one of the main regulating factors of apelin expression and secretion (Boucher et al 2005). Circulating apelin levels as well as ATexpression increase in obese and hyperinsulinemic subjects (Boucher et al 2005, Castan-Laurell et al 2008. Plasma apelin levels are also raised in morbidly obese (Heinonen et al 2005) and type 2 diabetic (Soriguer et al 2009) subjects.…”
Section: Introductionmentioning
confidence: 99%
“…The high apelin concentrations can be modulated by weight loss. Indeed, it was shown that diet-induced weight loss reduces plasma apelin levels in women with moderate obesity (Castan-Laurell et al 2008), but not significantly in patients with metabolic syndrome (Heinonen et al 2009). Bariatric surgery leads to a significant decrease in plasma apelin in morbidly obese subjects with impaired fasting glucose or type 2 diabetes before surgery (Soriguer et al 2009).…”
Section: Introductionmentioning
confidence: 99%